Generic drugs, its reliability and acceptance: a literature review (Research, Society and Development, 2023)
Medicines are an important strategic source of action in health, used for the treatment, cure or prevention of numerous clinical conditions. The choice of a drug by consumers is strongly influenced by several factors, which can be economic, cultural, social, personal or psychological. Since the implementation of generic drugs, until the present day, there are still doubts on the part of users, who judge the quality of the product, this is due to little information available, lack of knowledge and incentive. With the advancement of technology, knowledge about the generic is increasing, making users more reliable and starting to buy this medicine, not to mention the role that the pharmacist has been playing, guiding users regarding the quality and effectiveness of the same. and promoting the rational use of medicines. Actions and participation of the pharmaceutical professional are extremely relevant for society, and this professional is responsible for guiding, solving doubts and guaranteeing the safety and rational use of medicines. This study aimed to assess knowledge and acceptance of generic drugs through a literature review. The use of generic names facilitates the prescription and dispensing of medications to patients and communication between health professionals. The present work was a literature review that aimed to synthesize results obtained in research on a theme or issue, in a systematic, orderly and comprehensive manner. The publication year will be limited between the years 2017 to 2022.